Analysis of Instagram Use by Libraries in Responding to the COVID-19 Pandemic : A Case Study of University Libraries in Indonesia - Syadza Millati Azka; Taufik Asmiyanto; Parveen Babbar (Record and Library Journal, 2023)
Background of the study: Today the use of social media is so massive that it is not limited to the personal sphere. Business institutions and corporations also utilize social media always to be able to connect with their target users for marketing activities and to communicate their products. Purpose: It aims to analyze Instagram social media usage patterns by college libraries during the COVID-19 pandemic, especially on their Instagram accounts. In this study, there were four universities, both public and private, which analyzed the usage patterns of their Instagram. Method: This research analyzes the usage and utilization patterns of Instagram by university libraries in Indonesia during the COVID-19 pandemic in two stages, the content analysis method is employed to identify information on Instagram accounts of universities W, X, Y, and Z. Findings: There was a significant change in the pattern of using Instagram libraries between before and during the COVID-19 pandemic regarding the number and category of posts used. The number of posts related to COVID-19 is dominated by information about temporary remote services. Conclusion: The entire library actively socializes while encouraging users to takeadvantage of remote services and their on-site. However, the library is still not optimal